Professional Standards and SOPs in Legal Protection and Medical Service Quality in Indonesia - Maulidya, Gina Nada; Onggo, Prisilia; Suparman, Odang (Research Horizon, 2026)
Medical professionals face increasing legal challenges due to allegations of malpractice, highlighting the need for clear legal protection mechanisms. This study aims to provide legal protection for medical professionals who deliver medical services in accordance with professional standards and Standard Operating Procedures (SOPs), based on a case study of the Makassar District Court Decision Number 1441/Pid.Sus/2019/PN Mks. The research employs a normative juridical method with a qualitative approach and doctrinal analysis of the court decision. Data sources consist of primary and secondary legal materials, which are analyzed descriptively, comparatively, and interpretatively. The findings indicate that the defendant was acquitted of all charges due to a lack of legally convincing evidence of a law violation and the absence of a final decision from the Indonesian Medical Disciplinary Honorary Council regarding professional misconduct. The application of the principle lex specialis derogat legi generali serves as the legal basis, establishing that Law Number 29 of 2004 concerning Medical Practice takes precedence over general criminal provisions, such as Article 360 of the Indonesian Criminal Code. The study concludes that medical personnel should receive legal protection as long as medical actions are performed in accordance with applicable professional standards, operational procedures, and professional ethics.